Peningkatan Nilai Ekonomi Desa Mojokusumo Melalui Diversifikasi Produk Berbasis Singkong Studi Kasus : Pengolahan Tepung Alami - Irham Miftakhul Jannah; Ayu Sinta Apriliah; Mitha Silvia; Regina Raisa Sari; Rahmat Debianto; Dela Nadelya; Sella Novita Sari; Annisa Rahma Pramudya Wardhani; Nico Riyan Afandi; Mochamad Nurul Iman; Amelya Faradilla Wardani; Nauval Ramadhani; Dedi Tri Waludin; Febriannada Abiyyu Alammi Wafa; Asta Lycha Shenandy; Bernika Indiagusti Ivada; Sofian Ardiansyah; Achmad Wahid; Winda Agus Prihatiningsih; Putri Alfiani Islamiyah; Fianny Fianny; Adinda Firdaus Zakiah; Yhoga Maulana Syafi'I; M Nizar Hanafi; Muhammad Syaifulloh (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The natural resources produced by Mojokusumo village are very abundant, one of which is the agricultural product, cassava. Unfortunately, the agricultural products have not been fully utilized, mostly processed into boiled cassava or fried cassava. With these conditions, this society needs to be educated through training on the diversification of cassava derivative products so that they can have high market value and provide economic improvement for the village of Mojokusumo. The purpose of this training is to raise awareness and knowledge among the society of Mojokusumo Village, especially the PKK (Family Welfare Movement) members, regarding the potential for diversifying cassava-based products, thereby increasing the added value of local commodities. The method in this community service activity uses a descriptive qualitative approach, which includes socialization, training, and direct assistance in product diversification. The result of the product diversification activities of cassava processing derivatives is natural flour (tapioca). Other results include 1) the ability to effectively enhance the knowledge and skills of the Mojokusumo Village community in processing cassava into natural flour, and 2) the ability to contribute to the development of entrepreneurship that can increase the economic value of Mojokusumo Village.